2001
DOI: 10.1161/hq1201.100228
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage Analysis of Lipids in the Hypertension Genetic Epidemiology Network (HyperGEN) Blood Pressure Study

Abstract: Abstract-Full genome scans were performed for quantitative lipid measurements in 622 African American and 649 white sibling pairs not taking lipid-lowering medications who were ascertained through the Hypertension Genetic Epidemiology Network (HyperGEN) of the National Heart, Lung, and Blood Institute (NHLBI) Family Blood Pressure Program. Genotypes for 391 markers spaced roughly equally throughout the genome were typed by the NHLBI Mammalian Genotyping Service. Each of the phenotypes was adjusted for covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 46 publications
7
32
1
Order By: Relevance
“…HyperGEN study 19 showed a LOD score of 1.51 with FM in the present study. Positional candidate genes in the chromosome 1 region showing modest LOD scores (B1.5 for all three phenotypes) in this study include the sodium potassium-adenosine triphosphatase a2 (ATP1a2 [MIM 182340]) and b1 (ATP1b1 [MIM 182330]) genes.…”
Section: Discussionsupporting
confidence: 57%
“…HyperGEN study 19 showed a LOD score of 1.51 with FM in the present study. Positional candidate genes in the chromosome 1 region showing modest LOD scores (B1.5 for all three phenotypes) in this study include the sodium potassium-adenosine triphosphatase a2 (ATP1a2 [MIM 182340]) and b1 (ATP1b1 [MIM 182330]) genes.…”
Section: Discussionsupporting
confidence: 57%
“…It is more probable that another gene on chromosome 19 or 12 directly affects urinary protein excretion, since a previous report in HyperGEN families failed to demonstrate linkage between markers on chromosome 19 and serum LDL levels. 25 …”
Section: Discussionmentioning
confidence: 99%
“…ApoB100 plays a critical role in the binding of Lp-PLA 2 to the LDL particle [3], and is the defining protein of LDLs. Genome screen using data from human populations have localized QTLs to adjacent regions of HSA2p for apoB [10,30], total cholesterol [10,31], and familial combined hyperlipidemia [10,30,32]. Additionally, Austin et al [33] reported APOB effects on multiple lipoprotein traits comprising an atherogenic phenotype: peak particle diameter of LDL, triglycerides, and HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%